Morphological and Molecular Characterization of Tylenchorhynchus clarus Allen, 1955 and T. zeae Sethi & Swarup, 1968 (Rhabditida: Telotylenchidae) from Iraq - Jumaah Ahmed Malik; Azimi Sedighe (Journal of Nematology, 2022)
During a survey on the biodiversity of plant-parasitic nematodes in Misan province (southeast Iraq), Tylenchorhynchus clarus and T. zeae were discovered around the rhizosphere of sugarcane and pumpkin, respectively. The morphological and morphometric data were provided for the recovered species. The morphological characters of both populations are in agreement with the type populations and other populations of them. To the best of our knowledge, this is the first report of these two species from Iraq, and a first report of the association of T. zeae with pumpkin. Molecular phylogenetic analyses of the Iraqi populations of T. clarus and T. zeae using the D2–D3 expansion segments of 28S rDNA and internal transcribed spacer (ITS) rDNA sequences using Bayesian inference (BI), showed they form maximally supported clades with other sequences of both species.